2021
DOI: 10.1021/acsami.1c05989
|View full text |Cite
|
Sign up to set email alerts
|

Iron Phosphide Confined in Carbon Nanofibers as a Free-Standing Flexible Anode for High-Performance Lithium-Ion Batteries

Abstract: Iron phosphide with high specific capacity has emerged as an appealing candidate for next-generation lithium-ion battery anodes. However, iron phosphide could undergo conversion reactions and generally suffer from a rapid capacity degradation upon cycling due to its structure pulverization. Chemomechanical breakdown of iron phosphide due to its rigidity has been a challenge to fully realizing its electrochemical performance. To address this challenge, we report here on an enticing opportunity: a flexible, free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The characteristic peaks of FeP 2 gradually disappear in the first lithiation process, but don't gradually increase and return to the initial state of FeP 2 in the following delithiation processes, suggesting that the electrochemically formed FeP 2 is amorphous. 30 After the activation of the first cycle, the reduction peak moves to about 0.59 V, and the oxidation peak moves to about 1.29 V. Such a voltage shift can be ascribed to the strain and structure changes of the FeP 2 crystal in the initial lithiation process. A similar phenomenon was also observed for FeP 2 NAs@C, FeP 2 NAs, and other conversion-based anode materials (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The characteristic peaks of FeP 2 gradually disappear in the first lithiation process, but don't gradually increase and return to the initial state of FeP 2 in the following delithiation processes, suggesting that the electrochemically formed FeP 2 is amorphous. 30 After the activation of the first cycle, the reduction peak moves to about 0.59 V, and the oxidation peak moves to about 1.29 V. Such a voltage shift can be ascribed to the strain and structure changes of the FeP 2 crystal in the initial lithiation process. A similar phenomenon was also observed for FeP 2 NAs@C, FeP 2 NAs, and other conversion-based anode materials (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Such good rate performance of FeP 2 NPs@CK is better than that of carbon-coated phosphorus-rich iron phosphides in previously reported studies. 17,20,22,23,30,[33][34][35][36] To further demonstrate the stable cycle performance of FeP 2 NPs@CK, the cell was repeatedly cycled for 500 cycles at the high current density of 1 A g −1 , as depicted in Fig. 4f.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe forms diverse metal phosphides, including FeP 2 , [113] Fe 2 P, [114,115] and FeP. [116] Particularly, amorphous Fe-based phosphides buffered the volume changes, preventing performance degradation during cycles.…”
Section: Fe-based Phosphidesmentioning
confidence: 99%
“…3,4 Yang et al developed a Fe 2 P@carbon matrix using an electrospinning technique that showed a capacity of 573 mA h g À1 at the 300th cycle under 0.2 A g À1 . 5 Tang and co-workers synthesized a FeS 2 /Fe 7 S 8 -rGO composite through a solvothermal method that displayed 514 mA h g À1 after long-term cycling and good rate performance. 6 Liu et al prepared a graphene-supported MoS 2 nanosheet.…”
mentioning
confidence: 99%